Au nanorods-sensitized 1DPC for visible detection of NIR light. Issue 11 (6th March 2017) - Shen, Huaizhong; Wu, Yuxin; Wang, Wenjing; Su, Hongyang; Liu, Wendong; Zhang, Junhu; Zhang, Kai; Yang, Bai
Abstract : Au nanorod-sensitized one dimensional photonic crystal is fabricated for visible detection of near infrared light with fast response speed and flexibility. Abstract : Visible detection of electromagnetic waves is important. Herein, we propose a method to trace invisible near infrared (NIR) light by combining thermo-sensitive one-dimensional photonic crystals (1DPCs) and Au nanorods (NRs). Au NRs first absorb the NIR light and convert it into heat energy, then the temperature increase and the thermo-sensitive 1DPC produces a response through conformation transfer of the PNIPAm layer leading to the disappearance of its structural color, which is a quite obvious signal. We also realize the differentiation of NIR light belonging to a different wavelength range by building hybrid 1DPCs with Au NRs of different absorbance. The 1DPC/Au hybrid system is easy to prepare in a large area with low cost, the signal read-out can be observed by the naked eye and the polymer matrix also makes it a promising flexible device. We believe that such a device will be portable and has the potential to be used in various applications in daily life.